Caries prevalence and distribution in individuals aged 3–20 years in Jönköping, Sweden, over a 30-year period (1973–2003) - Anders Hugoson (IAPD and Blackwell, 2008)
In the 1950s to the 1960s, the high prevalence of caries was a major health problem in Sweden, particularly among children and adolescents 1–3 . Notably, caries progression was rapid in the occlusal surfaces of the first permanent molars 4 . At that time, no preventive dental care system was in place and, furthermore, restorative treatment was almost non-existent in primary teeth and inconsistent in young permanent teeth.